2012
DOI: 10.1007/s13197-012-0822-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and electrochemical properties of cultivated Pleurotus spp. and their sporeless/low sporing mutants

Abstract: Methanolic extracts of four cultivated edible mushrooms of Pleurotus spp. namely Pleurotus florida, Pleurotus sajor-caju, Pleurotus cystidiosus and Pleurotus djamor along with the sporeless/low sporing mutants of Pleurotus florida, and Pleurotus sajor-caju were analyzed for their antioxidant activity using different chemical assays. The electrochemical behaviors of these extracts were also analyzed using cyclic voltammetry and differential pulse voltammetry. Results showed that scavenging effects on 2,2-diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(32 reference statements)
1
8
2
Order By: Relevance
“…The total flavonoid content was 2.11 ± 0.19 and 1.26 ± 0.17 mg/g of extract, respectively. It was documented that major components of mushroom extract are phenolics and Pleurotus species exhibited different contents of total phenolic ranging from ~2 to >30 mg/g of extract [27,37,49]. In comparison with our earlier study [28], the results obtained for non-enriched mushrooms were slightly higher.…”
Section: Yield Total Phenolic Flavonoid and Ascorbic Acid Contentscontrasting
confidence: 77%
See 1 more Smart Citation
“…The total flavonoid content was 2.11 ± 0.19 and 1.26 ± 0.17 mg/g of extract, respectively. It was documented that major components of mushroom extract are phenolics and Pleurotus species exhibited different contents of total phenolic ranging from ~2 to >30 mg/g of extract [27,37,49]. In comparison with our earlier study [28], the results obtained for non-enriched mushrooms were slightly higher.…”
Section: Yield Total Phenolic Flavonoid and Ascorbic Acid Contentscontrasting
confidence: 77%
“…Some authors have stated that mushrooms contain mainly phenolics acids [7,50], while others reported a high amount of flavonoids in extracts [5,37,51]. The total flavonoid content in different species of Pleurotus was found at the level from 1.2 to 2.9 µg/g of extract [49], even to 7.79 mg/g of extract [37]. However, Vieira et al [27] did not detect flavonoids in P. ostreatus.…”
Section: Yield Total Phenolic Flavonoid and Ascorbic Acid Contentsmentioning
confidence: 93%
“…Menaga et al [27] reported that methanol extract of P. florida fruiting bodies showed reducing power of 0.911 at 0.5 mg/mL, which was significantly lower than the reducing power of our methanol extract of 1.88 at 0.5 mg/mL. The reducing power of a hot water extracts of Hypsizygus marmoreus was 0.99 at 5.0 mg/mL [28], whereas those of Agaricus bisporus, Pleurotus eryngii, Pleurotus ferulae and Pleurotus ostreatus showed reducing powers of 0.76, 0.75, 0.70, and 0.61 at 2.0 mg/mL, respectively [29]. Yoon et al [30] demonstrated that reducing power of methanol extract of Agaricus brasiliensis fruiting bodies was 1.54 at 6.0 mg/mL, which was lower than that of methanol extract from P. gilvus fruiting bodies at the same concentration tested.…”
Section: Bioactive Compoundscontrasting
confidence: 60%
“…varied contents of total flavonoids were observed, i.e. 1.2 ± 0.02 to 2.9 ± 0.07 mg/g of extract (Babu et al, 2014), 7.79 ± 0.04 mg catechin equivalent/g of extract (Sudha et al, 2012).…”
Section: Resultsmentioning
confidence: 93%
“…In other studies the total phenolic content ranged from <2 mg/g of dried mushroom to 15.7 ± 0.1 mg/g of extract for P. ostreatus (Elmastas, Isildak, Turkekul, & Temur, 2007;Palacios et al, 2011;Yang, Lin, & Mau, 2002), and from 22.7 ± 1.32 to 36.00 ± 0.44 mg/g of extract in other Pleurotus spp. (Babu, Pandey, & Rao, 2014;Sudha et al, 2012). The results obtained by Reis et al (2012) show that total phenolic content for P. ostreatus was 12.54 ± 0.18 GAE/g of extract, while for P. eryngii it was 7.14 ± 2.01 mg GAE/g of extract.…”
Section: Resultsmentioning
confidence: 93%